Enslavement, persisting through our political economy - Agarwal, Monty, 1968- (Cambridge Scholars Publishing, 2018)
Besides the most blatantly repulsive forms of slavery, exploitation is also perpetrated by limiting freedom of choice, undermining human dignity, destroying cultural identity, retarding financial security and partitioning opportunity and access to resources. The absence of a moral compass in the administration of political economies promotes the acquisition and vigorous defense of a monopoly over resources, leading to unsustainable, gross imbalances. It has provided us with every single form of the enslavements mentioned above. This book undertakes a process of discovery across civilizations an.